IPTEK BAGI MASYARAKAT UNTUK PERBAIKAN TEKNOLOGI PASCA PANEN PADI DENGAN DESAIN ALAT PENGAYAK BERAS SEDERHANA - Endang Suhesti; Ali Uraidy (Program Studi Agribisnis Fakultas Pertanian, 2015)
Rice production needed high cost and difficult process. Harvesting lost was about 20 , 5 %, but the quality of rice production was 15 % with low quality, bad taste and color. There were many machines have been produced for post-harvest handling. It helped the farmer for streamline in rice milling results so the price of rice suited the market needs. The purpose of IbM was increasing the farmers' knowledge on rice post-harvest handling, especially in determining the harvest time. The Agriculture officers have showed the different rice quality from different post- harvest handling. The result of IbM was rice sieving machine which was introduced to the partners so they could use it in rice milling production to increase the quality of rice. It would increase the opportunity in marketing the rice to non - traditional market. The IbM activities for technological improvement of post-harvest rice with design tools sieving machines have been implemented by training and mentoring include: socialization, training, and assistance to the farmers Kapongan and Gebangan village, Kapongan sib District which resulted by rice packaging and branding . The high interest of the community service program partners was a positive impact for the implementation of the program Implementation of the program capable of resulting in outcomes expected by this community service program, in the form of better marketing techniques through efforts to penetrate non-traditional markets.